Effect of ceramic cooling protocols and zirconia coloring on fracture load of zirconia-based restorations - Behnaz Ebadian; Ramin Mosharraf; Mahsa Abbasi (Wolters Kluwer Medknow Publications, 2018)
Background: Residual thermal stresses in dental porcelains can cause clinical failure. Porcelain cooling protocols may affect the amount of residual stresses within porcelain and also porcelain-zirconia bond strength. The objective of this study was to assess the effect of cooling protocols on the fracture load of porcelain veneered zirconia restorations. Materials and Methods: Forty zirconia bars (31 mm × 6.5 mm × 1.35 mm ± 0.1 mm) were fabricated by computer-aided design and computer-aided manufacturing technology. Half of the specimens were immersed in the coloring agent for 2 min before sintering (yellow group). Thus, the specimens were divided into two groups of white (W) and yellow (Y) samples (n = 20). Heat-pressed ceramic was applied to all bars. After pressing, half of the samples in each group were immediately removed from the oven (fast cooling) while the other specimens remained in the partially open door (30%) oven until the temperature reached to 500°C. Samples were thermocycled for 5000 cycles and subjected to modified four-point flexural strength test by a universal testing machine at a crosshead speed of 0.5 mm/min. Two-way ANOVA, One-way ANOVA followed by post hoc Tukey honest significant difference tests were used for data analysis (α = 0.05). Results: Fractures were cohesive in all samples (within the porcelain adjacent to the interface). Two-way ANOVA showed that the effect of cooling protocol on the fracture load of samples was statistically significant (P < 0.001). In addition, the fracture load of W and Y groups was significantly different (P < 0.001). The white slow group showed the highest fracture load (179.88 ± 23.43 N). Conclusion: Slow cooling protocol should be preferably applied for zirconia restorations. Coloring agent used in this study had a significant negative effect on fracture load.